Biocidal activity of Lippia origanoides H.B.K. (Verbenaceae) essential oil on Rhizoctonia solani: in vitro - Álvarez-Sánchez, David; Hurtado-Benavides, Andrés; Chaves-Morillo, Diana; Andrade-Díaz, Danita (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Rhizoctonia solani is a fungus that affects the production of tubers and vigor of potato plants, Solanum tuberosum L. The environmental consequences generated by its control have driven the search for less contaminating alternatives, and essential oils have great potential. The wild shrub Lippia origanoides H.B.K. (Verbenaceae) has been studied because of its attractive fungicidal properties in its essential extracts; therefore, the objective of this research was to evaluate the biocidal activity of L. origanoides essential oil on R. solani, in vitro. The oil extraction was carried out with steam dragging, the chemical composition was determined with Gas Chromatography-Mass Spectrometry (GC-MS), and, finally, the biocidal activity of the oil was evaluated with the dilution technique in the culture medium, which was complemented with the bioautography technique, which identified thymol as the major compound of the oil (60.7%), responsible for the fungus inhibition. The concentration 110 μL mL-1 limited the growth of R. solani by affecting the structures, thereby demonstrating the biocidal effect of this essential oil and its potential antifungal agent.